Radikale Bilder : 2. Österreichische Triennale zur Fotografie 1996 : Band 1 : Band 2. - Bianchi, Paolo; Braun, Alexander; Braun, Reinhard; Broeckmann, Andreas; Doswald, Christoph; Fenz, Werner; Gierstberg, Frits; Goffin, Torsten; Hoffmann, Justin; Korean, Basic; Lundström, Jan-Erik; Miller, John; et al. (Graz : Neue Galerie am Landesmuseum Joanneum, 1996)
Abdu'Allah, Faisal ; Allen, Clive ; Art in Ruins ; Barbier, Gilles ; Billingham, Richard ; Bitter, Sabine ; Weber, Helmut ; Blume, Anna & Bernhard Johannes ; Bond, Henry ; Bublex, Alain ; Buetti, Daniele ; Burkart, Manuela ; Chadwick, Helen ; Ensemble, Critical Art ; Csikvári, Petér ; Demand, Thomas ; Fritz, Darko ; Ganahl, Rainer ; G.R.A.M. ; Hofstetter, Michael ; Kaap, Gerald Van Der ; Kepenek, Ali ; Keser, Ivana ; Klauke, Jürgen ; McCollum, Allan ; Simmons, Laurie ; Miller, John ; Nebel, Christoph ; Neshat, Shirin ; Oursler, Tony ; Passow, Beate ; Pierson, Jack ; Prince, Richard ; Ristelhueber, Sophie ; Rondinone, Ugo ; Scherubel, Klaus ; Serralongue, Bruno ; Serrano, Andres ; Sherman, Cindy ; Sjöberg, Martin ; Westerlund, Sven ; Willats, Stephen
bibliografie
biografie
vertaling p. 174-183
Duits
Duits & Engels
Engels